Improving Student Achievement Through Group Guidance Services with Self-Management Techniques - Lahmuddin Lubis; Nurussakinah Daulay; Zainuddin Zainuddin (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The purpose of this article was to find out group guidance services with self-management techniques in improving the learning achievement of class X aliyah students at the AL-Muhlisin Islamic boarding school Batubata for the 2020/2021 academic year. The method used in this research is descriptive research method. The objects in this study were 5 students of class X-1 Madrasah Aliyah who were lacking in learning achievement. The sample used is class X-I students. Instrumentation of data collection in this study using observation, interviews, and documentation. Data analysis techniques in this study are data collection, data reduction, data presentation and drawing conclusions. The conduct of group guidance with self-management techniques to improve the learning achievement of class X aliyah students at the Al-Mukhlisin Batubara Islamic boarding school for the 2020/2021 academic year, has succeeded in increasing student learning achievement, this can be seen by the increase in student values ​​and knowledge when in teaching and learning activities, so it can be concluded that group guidance with self-management techniques is very effective in improving student achievement in class X-I aliyah at the Al-Mukhlisin Batubara Islamic boarding school for the 2020/2021 academic year.